PENGARUH DISIPLIN DAN MOTIVASI KARYAWAN TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN PADA PABRIK KELAPA SAWIT PT. PERKEBUNAN NUSANTARA V UNIT BISNIS SUNGAI GALUH - Tampubolon, Jos Irwan; Isyandi, B.; Indarti, Sri (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2016)
This study aimed to analyze the influence of Discipline and motivation oemployee job satisfaction. Discipline influence on job satisfaction. Motivatio influence on job satisfaction and job satisfaction influence on employe performance at Palm Oil Mill PT. Perkebunan Nusantara V Business Unit Sunga Galuh.The population in this study were employees of Palm Oil Mill PT. Perkebuna Nusantara V Business Unit Sungai Galuh amount to 162 people. The magnitud of the sample to be used is 115 people. Data analysis and interpreting the data descriptive analysis method and analysis methods verification. Descriptiv analysis method is used to describe the characteristics of respondents and th research variables, whereas the verification method used to test the researc hypotheses by using relevant statistical tests. While the verification method use in this study is a two-stage regression.The results of the study Discipline and Motivation effect on job satisfaction. Thi shows that the Discipline and motivation are very important in determining jo satisfaction, the better discipline and motivation will determine job satisfaction i positive, and vice versa. Discipline affects the Employee Satisfaction on. Thi indicates that Discipline is very important, the higher the level of employe discipline will determine job satisfaction is positive, and vice versa. Motivatio affects the Employee Satisfaction on. This suggests that the motivation is ver important, the higher the motivation will determine employee job satisfaction i positive, and vice versa, and job satisfaction affect the performance Employees a Palm Oil Mill PT. Perkebunan Nusantara VBusiness Unit Sungai Galuh. Thi shows that job satisfaction is so important to cause employees who are satisfie will improve performance.